5α-dihydrotestosterone abrogates sex bias in asthma like features in the mouse. (August 2020) - Cerqua, Ida; Terlizzi, Michela; Bilancia, Rossella; Riemma, Maria A.; Citi, Valentina; Martelli, Alma; Pace, Simona; Spaziano, Giuseppe; D'Agostino, Bruno; Werz, Oliver; Ialenti, Armando; Sorrentino, Rosalinda; et al.
Graphical abstract: Highlights: 5α-dihydrotestosterone is involved in sex bias in asthma disease. 5α-dihydrotestosterone inhibits allergen-induced bronchial hyperreactivity in females. 5α-dihydrotestosterone inhibits mast cell activation/degranulation induced by allergen. Abstract: Androgen levels inversely correlate with the incidence, susceptibility and severity of asthma. However, whether male sex hormones such as 5α-dihydrotestosterone (DHT) have beneficial effects on asthma symptoms and/or could affect asthma susceptibility have not been investigated. DHT administration to female mice, during the sensitization phase, abrogates the sex bias in bronchial hyperreactivity. This effect correlates with inhibition of leukotriene biosynthesis in the lung. DHT significantly inhibits also other asthma-like features such as airway hyperplasia and mucus production in sensitized female mice. Conversely, DHT does not affect plasma IgE levels as well as CD3 + CD4 + IL-4 + cell and IgE + c-Kit + cell infiltration within the lung but prevents pulmonary mast cell activation. The in vitro study on RBL‐2H3 cells confirms that DHT inhibits mast cell degranulation. In conclusion, our data demonstrate that immunomodulatory effects of DHT on mast cell activation prevent the translation of allergen sensitization into clinical manifestation of asthma.